Dynamic creation of topological solitons via nematic vortex lines - Xinda Zheng; Jing Zhang; Wentao Tang; Zhawure Asilehan; Zijun Chen; Jinghua Jiang; Rui Zhang; Chenhui Peng (Proceedings of the National Academy of Sciences, 2026)
Topologically protected solitonic structures have garnered significant attention in condensed matter physics due to their unique stability and potential applications in next-generation technologies such as high-density data storage and spintronics. Vortex lines, another class of topological defects, are ubiquitous in nematic liquid crystals (LCs) and provide a versatile platform for studying topological phase transitions. A key challenge in the field is understanding how to transition between these fundamentally distinct topological objects. By combining experimental observations and numerical simulations, we demonstrate that vortex lines can transition into soliton strings through interactions with wedge or twist vortices of topological charge ± 1 / 2 . By anchored patterns on surfaces, we are able to control topological structures of soliton strings. Using laser tweezers, we manipulate vortex lines to dynamically create and annihilate soliton strings, revealing the compatibility between vortices and solitonic structures. The soliton ring with continuously varying topological profiles can be created by using two adjacent vortex loops with Möbius strip topology. We also create complex topological configurations, such as arbitrary shaped hybrid structures composed of intertwined vortex lines and soliton strings, by leveraging out-of-equilibrium transitions. These findings pave the way for designing smart materials with tailored topological properties.